2013
DOI: 10.1007/s13277-013-1505-5
|View full text |Cite
|
Sign up to set email alerts
|

Letter regarding Wang et al. entitled “Effects of murine double minute 2 polymorphisms on the risk and survival of osteosarcoma: a systemic review and meta-analysis”

Abstract: Wang et al. [1] conducted a meta-analysis to assess the effects of murine double minute 2 (MDM2) polymorphisms on osteosarcoma risk and survival of patients with osteosarcoma. They calculated the pooled odds ratio (OR) or hazard ratio (HR) with 95 % confidence intervals (95 % CIs) by using different effects models and concluded that MDM2 polymorphisms have some effects on the risk of osteosarcoma but have no effect on the survival of patients with osteosarcoma. Before their results can be accepted, we would l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 3 publications
1
3
1
1
Order By: Relevance
“…In agreement with Liu et al [2], we also think that further studies with large samples are still needed to assess the effects of MDM2 polymorphisms on the risk and survival of osteosarcoma.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…In agreement with Liu et al [2], we also think that further studies with large samples are still needed to assess the effects of MDM2 polymorphisms on the risk and survival of osteosarcoma.…”
supporting
confidence: 91%
“…The authors concluded that MDM2 polymorphisms had effects on the risk but had no effect on the survival of patients with osteosarcoma. In a recent letter to the editor, Liu et al [2] detected several weaknesses in the meta-analysis. Firstly, they criticize the small number of papers included in the analyses, which could lead to false significant associations.…”
mentioning
confidence: 99%
“…Since these negative results were different from previous published results, we decided to perform a deep revision of data published in the literature and realized a new meta-analysis. The results showed no association, in contrast to another metaanalysis previously published, (13) in which some inaccuracies were detected (14,15). The differences between both metaanalyses could be due to the fact that our study included two new populations, but they can also be explained because different data from the original articles were selected.…”
Section: Discussioncontrasting
confidence: 84%
“…Nevertheless, some inaccuracies were detected in the study. Among others, the lack of information in the methods used to select the studies and extract the genotyping data and the inclusion of other types of bone tumors in the meta-analysis (not only OS) (14,15).…”
Section: Systematic Review Nature Publishing Groupmentioning
confidence: 99%
See 1 more Smart Citation